Sun Kings cross the outback [solar powered vehicles marathon]. - Zorpette, G.
The University of Michigan's solar racing team showed its mettle in the gruelling World Solar Challenge marathon. To win the race required state-of-the-art solar cells, batteries, electronics and the integration of mechanical, aerodynamics, and materials science
Keywords: University of Michigan; World Solar Challenge marathon; Aerodynamics; Batteries; Electronics; Materials science; Mechanical science; Solar cells; Solar powered vehicles